Dissociated response related to corticosteroids in lung cancer treated by immunotherapy: A case report. Issue 5 (24th March 2021) - Thomas, Quentin Dominique; Sinoquet, Léa; Maraver, Antonio; Quantin, Xavier
Abstract: We report the case of a patient with a complete metastatic adrenal response on Pembrolizumab for metastatic lung cancer. Treatment with a systemic corticosteroid‐induced a time‐dependent progression at his metastatic site. Surprisingly, after stopping the corticosteroid, we observed a new complete response in long‐term adrenal metastases. Abstract : The administration of systemic corticosteroid therapy for a prolonged period in patients undergoing treatment with immune checkpoint inhibitors for metastatic lung cancer can have a direct impact on the tumor response and may be reversible.